Effects of dietary magnesium supplementation on physiological parameters in captive cheetahs (Acinonyx jubatus) at Hoedspruit Endangered Species Centre (HESC) - Webb, E.C. (Edward Cottington) (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2012.